2020
DOI: 10.1159/000508102
|View full text |Cite
|
Sign up to set email alerts
|

Management and Prognosis of Localized Duodenal Neuroendocrine Neoplasms

Abstract: <b><i>Introduction:</i></b> The characteristics, prognostic factors, and management of duodenal neuroendocrine neoplasms (dNEN) are ill-defined, given their rarity. Whether nonsurgical management might be appropriate for patients with nonmetastatic dNEN and a good prognosis, as is the case for pancreatic NEN (pNEN), is unknown. We aimed to describe the management and prognosis of nonmetastatic dNEN patients. <b><i>Methods:</i></b> All consecutive patients with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 6 , 7 Genetic alterations may explain their clinical heterogeneity, divergence for treatment response, and prognosis. 8 However, more studies are need to provide further details on genetic characteristics of GI‐NENs. Genetic alterations, identified through next‐generation sequencing (NGS), may provide the unprecedented opportunity to investigate genomic differences in the various histological types of GI‐NENs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 Genetic alterations may explain their clinical heterogeneity, divergence for treatment response, and prognosis. 8 However, more studies are need to provide further details on genetic characteristics of GI‐NENs. Genetic alterations, identified through next‐generation sequencing (NGS), may provide the unprecedented opportunity to investigate genomic differences in the various histological types of GI‐NENs.…”
Section: Introductionmentioning
confidence: 99%
“…A few noteworthy findings had indicated the possible genomic characteristics of GI‐NENs 6,7 . Genetic alterations may explain their clinical heterogeneity, divergence for treatment response, and prognosis 8 . However, more studies are need to provide further details on genetic characteristics of GI‐NENs.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, they are more frequently associated with neurofibromatosis type 1 (NF1) and tend to occur in younger individuals [4]. Although most studies showed a lack of significant prognostic differences between Amp-NENs and non-Amp-Duo-NENs, especially when only well-differentiated neuroendocrine tumors (NETs) were considered [3][4][5][6][7][8][9][10], Amp-NENs were shown to display a more aggressive behavior with a trend towards reduced overall survival in some studies [11][12][13][14][15]. In addition, there are several histologic differences between Amp-NENs and non-Amp-NENs.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with tumor diameters of 1–2 cm have a higher likelihood of lymphatic metastasis 1 , 4 and it is challenging for endoscopists to deal with the d-NETs because they have a thinner wall in the duodenum than in other gastrointestinal tracts 10 . Therefore, the rate of surgical resection is currently higher for these patients as our results (214/159).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of d-NETs has increased significantly in recent years with the popularization of endoscopy. World Health Organization (WHO) classification, lymph node status and tumor size have historically been important prognostic factors 1 4 . A recent study 1 reported that the incidence of lymph node metastasis (LNM) increased with d-NETs size (≤ 1 cm: 40.0% vs 1–2 cm: 65.7% vs > 2 cm: 80.0%).…”
Section: Introductionmentioning
confidence: 99%